1992
DOI: 10.1007/bf02536472
|View full text |Cite
|
Sign up to set email alerts
|

The dual effect of oxidation on lipid bilayer structure

Abstract: Sphingomyelin membranes were prepared with different levels of oxidative damage caused by tert-butyl hydroperoxide (TBH). Temperature-induced changes in membrane hydrocarbon chain packing (phase transitions) were monitored using infrared spectroscopy. Lipid phase transition characteristics were evaluated from thermodynamic parameters fitted to the experimental transition curve data. At temperatures below the lipid phase transition Tc, hydrocarbon chains pack in an ordered state whereas above the Tc the hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Beyond the studies reviewed in 1984, multiple reports have demonstrated the relevance of lens lipid oxidation with age and cataract formation (Ahuja et al, 1999;Borchman et al, 1992Borchman et al, , 2000Borchman and Yappert, 1998;Girao et al, 1998;Jernigan et al, 1993;Ogiso et al, 1993;Simonelli et al, 1996;Zhang et al, 1999). This topic will not be discussed in detail, but many studies have demonstrated that the propensity of lens mammalian membranes toward degradation is inversely related to the contents of sphingolipids (Babizhayev et al, 1988;Bhuyan and Bhuyan, 1994;Bhuyan et al, 1991Bhuyan et al, , 1996Borchman et al, 2000;Borchman and Yappert, 1998;Girao et al, 1998;Reddy et al, 1999;Simonelli et al, 1996;Varma et al, 1994).…”
Section: Why Is the Depletion Of Pcs And Other Glycerophospholipids Fmentioning
confidence: 97%
“…Beyond the studies reviewed in 1984, multiple reports have demonstrated the relevance of lens lipid oxidation with age and cataract formation (Ahuja et al, 1999;Borchman et al, 1992Borchman et al, , 2000Borchman and Yappert, 1998;Girao et al, 1998;Jernigan et al, 1993;Ogiso et al, 1993;Simonelli et al, 1996;Zhang et al, 1999). This topic will not be discussed in detail, but many studies have demonstrated that the propensity of lens mammalian membranes toward degradation is inversely related to the contents of sphingolipids (Babizhayev et al, 1988;Bhuyan and Bhuyan, 1994;Bhuyan et al, 1991Bhuyan et al, , 1996Borchman et al, 2000;Borchman and Yappert, 1998;Girao et al, 1998;Reddy et al, 1999;Simonelli et al, 1996;Varma et al, 1994).…”
Section: Why Is the Depletion Of Pcs And Other Glycerophospholipids Fmentioning
confidence: 97%
“…Oxidized lipids contain hydrophilic groups such as hydroxyl and hydroperoxyl moieties located on the hydrophobic hydrocarbon chains that disrupt lipid-lipid interactions, causing structural irregularities in the membrane ( 60 ). Phospholipase A2 degrades lipids at points in the membrane that exhibit such structural irregularities ( 61 ).…”
Section: Phospholipase A2 Oxidation and Changes In Lipid Compositionmentioning
confidence: 99%
“…This then alters the lipid composition and mechanical packing of the vesicle that subsequently forms [16][17][18][19]. As a result, there could be changes in liposomal permeability [20][21][22] and the subtle interactions between lipids and membrane proteins and/or other amphiphilic molecules [16].…”
Section: Introductionmentioning
confidence: 99%